The good and bad example and example in the Holy Book - م.م. علي يوسف عبد الزهرة (Journal of College of Education, 2023)
Exemplary example is one of the most important and prominent parenting methods. And if what is intended in the human society is to reach the stage of producing a healthy and useful individual for society, then this will not be achieved without working to make individuals healthy and useful, then example is the most important means to achieve this. If we go back to human history and the history of religions, we will find that role models have played this educational role, as they are useful in conveying correct ideas, values, and behaviors to others. This issue may indicate the ineffectiveness of some indoctrination in the educational process. The individual may not be convinced or believe if he finds that the prompter does not believe, believe, or be certain, but when we present the role model as a basic model for education, the influence on souls will be stronger inevitably.On the other hand, there is a bad example that could deviate an entire generation from its moral, progressive and scientific path, as we see in the trivial, unconscious models that appear on television and social media.
Keywords: good example, the Holy Quran, bad example, good example